2016
DOI: 10.28991/cej-2016-00000059
|View full text |Cite
|
Sign up to set email alerts
|

Geotechnical Properties of Lateritic Soil Stabilized with Ground-Nut Husk Ash

Abstract: This study assesses the geotechnical properties of lateritic soil stabilized with Ground-nut Husk Ash. Preliminary tests were carried out on the natural soil sample for identification and classification purposes, while consistency limits tests were thereafter carried out as well. Engineering property tests such as California Bearing Ratio (CBR), Unconfined Compressive Strength (UCS) and compaction tests were performed on both the natural soil sample and the stabilized lateritic soil, which was stabilized by ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…A pozzolana is a silicious material which in itself does not possess cementitious properties but will in finely divided form and in the presence of water react with calcium hydroxide Ca(OH)2. The PBA qualifies as a pozzolana since the percentage sum of its SiO2, Al2O3 and Fe2O2 components (76.9%) exceeds the minimum requirement of 50% [21]. The PBA is the natural, very finely divided, highly reactive type of pozzolana.…”
Section: Compaction Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pozzolana is a silicious material which in itself does not possess cementitious properties but will in finely divided form and in the presence of water react with calcium hydroxide Ca(OH)2. The PBA qualifies as a pozzolana since the percentage sum of its SiO2, Al2O3 and Fe2O2 components (76.9%) exceeds the minimum requirement of 50% [21]. The PBA is the natural, very finely divided, highly reactive type of pozzolana.…”
Section: Compaction Testsmentioning
confidence: 99%
“…This result is similar to that obtained by [1] in which the optimum CBR occurred at 15% PBA content. This is attributed to the fact that PBA in its finely divided form in the presence of water reacts with Ca(OH)2 to form cementitious compounds [21]. It was observed that after stabilization with PBA, the CBR of the lateritic soil+PBA mixture increased from 3% to 8% and 32% respectively for the soaked and unsoaked samples.…”
Section: Cbrmentioning
confidence: 99%
“…Assessing the impact of stabilizers on soil strength involves looking at changes in consistency limits, compaction characteristics, undrained cohesion, and modulus of elasticity. The investigation of the durability properties of stabilized soil employed the augmentation of undrained shear strength over many days of curing by increasing the percentage of cement [1][2][3][4][5][6]. The stabilized soil's strength and uniformity increased to a suitable level [1].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of ash from the ground-nut husk on the geotechnical properties of a lateritic soil was studied in [8]. Proctor compaction, CBR, and UCS tests were performed on both unstabilized and stabilized soil with ground-nut husk ash.…”
Section: Introductionmentioning
confidence: 99%